Crime and empire, 1840 - 1940: criminal justice in local and global context - Godfrey, Barry S. (Willan Publ., 2005)
This book is a major contribution to the comparative histories of crime and criminal justice, focusing on the legal regimes of the British empire during the nineteenth and early twentieth centuries. Its overarching theme is the transformation and convergence of criminal justice systems during a period that saw a broad shift from legal pluralism to the hegemony of state law in the European world and beyond. Chapters in the book present a variety of approaches, ranging from global discussions of key issues and developments to an exploration of local case studies and their relationship to these broader themes. Overall they reflect thinking and developments within criminological, historiographical and post-colonial approaches. Crime and Empire 1840-1940 reflects a growing interest in the history of criminal justice on the past of both criminologists and historians. The legacy of colonialism continues to be disputed in the courts and elsewhere.